2007
DOI: 10.1001/archpedi.161.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Motivational Interviewing to Prevent Childhood Obesity

Abstract: Motivational interviewing by pediatricians and dietitians is a promising office-based strategy for preventing childhood obesity. However, additional studies are needed to demonstrate the efficacy of this intervention in practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
247
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(254 citation statements)
references
References 21 publications
6
247
0
1
Order By: Relevance
“…37 Instead, a more patient-centered approach may be more effective. 37,38 This approach is characterized by asking questions, assessing parental readiness, and working with parents to make changes. Using this patient-centered approach may help decrease the feeling of blame and make the discussion seem more relevant to the individual child, thereby, increasing the likelihood that behavior change may occur.…”
Section: Discussionmentioning
confidence: 99%
“…37 Instead, a more patient-centered approach may be more effective. 37,38 This approach is characterized by asking questions, assessing parental readiness, and working with parents to make changes. Using this patient-centered approach may help decrease the feeling of blame and make the discussion seem more relevant to the individual child, thereby, increasing the likelihood that behavior change may occur.…”
Section: Discussionmentioning
confidence: 99%
“…However, other recent interventions in primary care or general medicine settings have been effective [7,[80][81][82][83], though challenging to implement [84], so this area may also be worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In addition, several clinic-based interventions have shown positive effects, such as modest weight loss, improved diet quality, and increased physical activity. [9][10][11][12][13] Social cognitive theory suggests that ones' self-efficacy (confidence in one's ability to do a given behavior), outcome expectations (a person's expectation that performing an action will lead to a specific result), and perceived environmental barriers and facilitators can influence behavior. 14 Previous studies exploring providers' attitudes and beliefs have been descriptive in nature and have shown that providers believe that childhood obesity needs treatment, affects chronic disease risk, and deserves their attention.…”
Section: Introductionmentioning
confidence: 99%